Smart new world: an enquiry into social acceptability of future and emerging autonomous systems for the home - Nilsson, Tommy (2020)
The convergence of multiple technologies, including sensors, embedded computing, real-time analytics and machine learning, is in the process of enabling system solutions capable of perception, decision-making and actuation without depending on direct human control or oversight. A widespread adoption of such autonomous systems has been suggested to make our lives more efficient, convenient and healthy, with the domestic context being frequently described as one of the main potential growth areas in this domain. However, it is important to treat such predictions with a degree of caution as they are based on mere extrapolations from the current trends in technical progress that fail to take into account (known and unknown) non-technical pitfalls that might yet impact mainstream adoption. Indeed, research indicates the adoption of domestic autonomous systems is already being hampered by a variety of critical issues including an impaired sense of trust, privacy and security. This thesis elaborates such human challenges further by exploring the manner in which prospective users relate to the notion of having their homes augmented through autonomous systems, along with the key points of friction this might give rise to. It makes two contributions. The first one is of a methodological nature and focuses on the use of envisioning approaches centred around provocative and deliberately contrasting scenarios of future domestic autonomous systems. These are used to drive an innovative workshop-based approach to “breaching experiments”; a sociological research method employed to surface tacit and unspoken background expectancies implicated in the organisation of everyday life. We argue that understanding and respecting such background expectancies is instrumental for the design of socially acceptable future autonomous technologies. The other contribution is substantive, produced through participants’ efforts to repair the incongruity or “reality disjuncture” created by the contrasting scenarios. Our analysis of workshop participants’ responses to the scenarios revealed background expectancies centring on 4 key themes in the form of coordination and the need to build the human into the behaviour of autonomous systems, control and the need to protect human agency, computational accountability and the legibility of autonomous system behaviour, as well as social accountability and the compliance of autonomous behaviours with social norms. We conclude by arguing that each of these key topics is formed by and brings with it a range of ancillary requirements that impact the adoption of autonomous systems in the home. This in turn opens up design possibilities enabling developers to gear autonomous domestic systems in with the non-technical expectations that govern their uptake in everyday life.